Unlocking the Development of Hydropower Potential - Dhungel, Kamal Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Nepal is rich in hydropower amounted to 42 GW. But it is poor in terms of per capita electricity consumption amounted to 106 KWh which keeps Nepal in a lowest position among the countries of South Asia. Harnessing this is a must for Nepal to run to the road to prosperity. Electricity use and economic growth move in the same direction indicating an additional unit of growth requires additional multiple unit of electricity. There are a number of stakeholders of the rivers flowing inside Nepal. These rivers are being shared by four sovereign countries –originated in Tibet, enter Nepal and cross the border to flow in India and then in Bangladesh before reaching their final destiny. These rivers provide drinking water to the people of these countries. In addition, another option for the benefit to share of these rivers among the stakeholders is to develop hydropower in Nepal and export it to light the cities of the rest of countries. Nepal should prepare itself to make favorable environment-creating domestic market, reducing electricity generation cost, maintaining rule of law, creating stable policies, ending political instability, adopting appropriate pricing policies- to invite foreign direct investment needed to harness. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015